Fetal and Perinatal Determinants of Neonatal Mortality in the State of Qatar: A pilot phase univariate and multivariate analysis by PEARL Study - Eltinay, Sarrah; Rahman, Sajjad; Ansari, Walid El; Numeri, Nuha; Latiph, Emirah; Yousafzai, Muhammad Tahir (Journal of Postgraduate Medical Institute, 2013)
Objective: To analyze the fetal and perinatal determinants of neonatal mortality. Methodology: This was a pilot National Prospective cohort-study done from the data source of Qatar PerinatalRegistry (Q-Peri-Reg). National data on total deliveries, live births and neonatal mortality was ascertainedfrom Qatar's national perinatal registry for the study period (1st January to 30th June 2011). Dataon gender, fetal growth, birth weight, gestational age, presentation at birth, mode of delivery, APGAR scoreat one and five minutes and the need for delivery room resuscitation was ascertained for all neonatal deathsand a corresponding group of control babies and analyzed using a univariate and multivariate model. Results: The total deliveries during the study period were 9797 resulting in 9738 live births. The pretermdelivery rate was 4.9%(n=489) and low birth weight delivery rate 7.5%(n=739). The total numbers of neonataldeaths were 44(NMR 4.5/1000). Intrauterine growth restriction (IUGR), low birth weight, pretermdelivery, breech presentation, delivery by C-section, low APGAR score at one and five minutes and theneed for delivery room resuscitation were significantly associated (P<0.05) with neonatal mortality onunivariate analysis. Low birth weight (p<0.001), breech presentation (p=0.041) and the need for deliveryroom resuscitation (p<0.001) had significant association with neonatal mortality on multivariate analysis. Conclusion: Further improvement in neonatal survival is possible by decreasing the incidence of low birth weightand preterm deliveries as well as by better intra-partum care of breech presentations and fetuses in distress.